Low Prevalence of Toxoplasma gondii in Dogs From Central China - Zhu, Niuping; Yang, Liulu; Xin, Shilin; Huang, Wei; Jiang, Yibao; Yang, Yurong (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Toxoplasma gondii can infect almost all warm-blooded animals, including humans and dogs. Humans can become infected with T. gondii by petting dogs that have eaten or contacted infected cat feces. The aim of this study was to evaluate T. gondii infections in dogs from central China. From 2015 to 2021, a total of 536 dog samples (195 fecal, 81 hearts, and 260 serum samples) from Henan Province were collected. Heart juice or serum samples (n = 341) were tested for T. gondii antibodies using the modified agglutination test (MAT). Fresh myocardium (n = 6) and blood (n = 2) samples were bioassayed in mice. Results: The present study showed that 4.40% (15/341) of the dogs were seropositive for T. gondii by MAT (cut-off, 1:25) and 4.10% (8/195) of dog feces contained T. gondii DNA. No T. gondii DNA was found in any myocardium (n = 81) or blood (n = 2) samples. Viable T. gondii strain was not isolated from any myocardium or blood samples (n = 8). Compared to the prevalence of T. gondii antibodies in dogs sampled from 2015 to 2018, the prevalence significantly declined from 2020 to 2021 (P < 0.05). Gender and age were not risk factors for dogs infected with T. gondii in this study. However, compared to other sources, dogs from Zhoukou City (close to the Yellow River), or from pet shops showed significantly higher prevalence for T. gondii (P < 0.05). Conclusion: A total of 4.29% dogs were infected by T. gondii (23/536, 8 of 195 fecal samples, 2 of 260 serum and 13 of 81 heart juice samples ). This is the first survey of T. gondii infection in dog feces from China. Dogs were exposed to T. gondii, they could act as mechanical transmitters of T. gondii.